Effect of closing material on hearing rehabilitation in stapedectomy and stapedotomy: A finite element analysis - Lim, Jongwoo; Goo, Woonhoe; Kang, Dae Woong; Oh, Seung Ha; Kim, Namkeun (Frontiers in Neuroscience, 2023)
Stapedotomy or stapedectomy operations are often performed to treat otosclerosis. During the operation, the space created by bone removal is usually filled with a closing material such as fat or fascia. In this study, the effect of the Young’s modulus of the closing material on the hearing level was investigated. The results showed that the hearing level improved when the closing material was more compliant after stapedotomy. Further, an optimized Young’s modulus was identified for the closing material to achieve better hearing rehabilitation after a stapedectomy. Therefore, when the stapedotomy was performed using fat whose Young’s modulus is lowest among the potential closing materials, the hearing level recovered the best among all simulated cases.